Constraints and opportunities for innovation in the Moving to Work Demonstration Program. Issue 1 (2nd January 2020) - Walter, Rebecca J.; Colburn, Gregg; Yerena, Anaid; Pederson, Melony; Fyall, Rachel; Crowder, Kyle
ABSTRACT: The Moving to Work (MTW) Demonstration Program provides participating housing agencies with additional programmatic and operational flexibility that is used to achieve Congress's statutory goals. The MTW Demonstration Program is designed to provide agencies with the flexibility to pursue innovative activities, yet there are myriad constraints that alter the behavior of these agencies. This study uses evidence generated from interviews with personnel from MTW agencies to understand how they use MTW to address and overcome bureaucratic, resource, and market constraints to further their mission. The findings from this study enhance our understanding of MTW agencies, their decision-making, and how they innovate in a constrained environment. These results are relevant to a wide audience, including existing MTW agencies, public housing authorities that are considering MTW designation under the new expansion, housing researchers, as well as policymakers and practitioners who focus on federal housing policy and innovation in public agencies.